Índice geométrico e perda de carga localizada em conexões de emissores online - Cardoso, Gabriel G. De G.; Klar, Antônio E. [UNESP] (My University, 2014)
The objective of this research is to present a study on a relationship between the local head loss in connection of emitters in pipes with different diameters used in drip irrigation, with the online geometry of the emitter connectors, that allows an easy quantification of such head loss regarding of the size of the connectors. The experiment was carried out according to the Reynolds Numbers at a turbulent flow interval, obtained by the variation of the pipe outflow at a constant temperature of water. The results indicated that the friction factor of the Darcy-Weisbach equation can be estimated by the Blasius equation with the coefficients b = 0.300 and m = 0.25, for the above mentioned pipes. The head losses produced by the connections of the emitters, in relation to the pipe without emitter, was of 62%. A relationship between the kinetic load coefficient (K) and the index of blockage (IO) provoked by the online connector is presented by an algebraic equation which shows a coefficient of adjustment of approximately 96%.
Geometric index and local head loss in connection of online emitters
Keywords: Blasius equation; Local head loss; Reynolds number